Itab (Teguran) kepada Rasulullah SAW dalam Al-Qur’an: Telaah Kitab Tafsîr Al-Qur’an Al-‘Azhim - Kamila, Tsalitsa Noor (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2019)
The focus of this research is the interpretation of ‘Itâb (reprimand) to the Messenger of Allah in the Tafsîr Al-Qur’ân Al-‘Azhîm. The theme of ‘Itâb (reprimand) To the Prophet Muhammad was chosen because of this library research is descriptive-analytical. The primary source is the book of Tafsîr Al-Qur’ân Al-‘Azhîm. The secondary sources include writings that are relevant with this study. This research concludes: first, what is meant by 'Itâb (reprimand) is Allah's rebuke to the Messenger of Allah not because the Messenger of Allah was guilty or sinful, but ijtihad (his choice) violates what should be taken, even though ijtihad in Islam is permitted, but he is Prophet, Apostle, and as uswatun hasanah which is a good example for all people. As for the verse ‘Itâb (reprimand) to the Prophet Muhammad there were 12 places in the Qur'an according to the event. Q.S. an-Nisa '[4]: 105-113, Q.S. al-An'am [6]: 52-54, Q.S. al-Anfal [8]: 67-69, Q.S. at-Taubah [9]: 43-45, Q.S. at-Taubah [9]: 84, Q.S. al-Isra ’[17]: 73-77, Q.S. al-kahfi [18]: 23-24, Q.S. al-Hajj [22]: 52-54, Q.S. al-Ahzab [33]: 28, Q.S. al-Ahzab [33]: 36-40, Q.S. at-Tahrim [66]: 1-5, and Q.S. Abasa [80]: 1-16. Second, the interpretation of ‘Itâb (reprimand) to the Messenger of Allah in the Tafsîr Al-Qur’ân Al-‘Azhîm is based on mutawatir religious arguments that can be accounted for.